ILRI's role in promoting forage seed production - Hanson, Jean; Tedla, A. (International Center for Agricultural Research in the Dry Areas, 1998)
Research at ILRI has shown the value of incorporating forages and fodder species into sustainable farming systems, but the lack of available seed of adapted forage materials remains a major constraint to their adoption by smallholder farmers. Technical knowledge, access to seed, and economic incentives are essential. Recognizing the need to promote access to forage seed, ILRI (formerly ILCA) established a Herbage Seed Unit in 1989 to address the problem in Sub Saharan Africa and enhance the incorporation of forages in feed resource Development. It was envisaged that this would be achieved by strengthening national capacities to produce forage seed, and training scientists and technicians. This activity has now been expanded to provide a source of tropical forage seed for the establishment of national forage seed production in many countries. Past and current activities in forage seed production at ILRI are presented, and future plans for serving ILRI's global mandate are discussed